Taking the high road prehistoric habitation and exploitation in the mountains of East Crete : new evidence from an extensive survey - Kalantzopulu, Panagiōta ca. 20./21. Jh (PUL, Presses universitaires de Louvain, 2022)
This volume presents and discusses the results of an extensive survey that took place between 2014 and 2018 in the mountain ranges of East Crete. The survey of respectively the eastern part of the Dikte range and the Sitanos area above Zakros specifically targeted prehistoric cultural remains with the aim to investigate the extent at which this environmental zone was exploited during the Neolithic period and the Bronze Age. Based on the results of the fieldwork, the discussion focuses mostly on the Neopalatial period (Middle Minoan III Late Minoan IB) during which a systematic effort to occupy and exploit these two upland zones was especially evident. The study of architectural remains and movable finds that were sampled, documented and studied within the two areas allows a reconsideration of issues of political organization, labour mobilization, economic integration, production and specialization.
Literaturangaben
Keywords: Bronzezeit; Archäologische Landesaufnahme; Bodennutzung; Neolithikum; Siedlung; Kreta -- Ost